Construction and screening of L-valine high-yielding Escherichia coli using an artificial screening marker - Du, Bowen; Gao, Sheng; Kou, Daixue; Li, Yinuo; Li, Dan; Cao, Yongsheng; Yang, Cuiping; Guo, Chuanzhuang; Wang, Jianbin; Wang, Junqing; Li, Nan (Frontiers in Microbiology, 2025)
IntroductionL-valine is commonly utilized in cosmetics, pharmaceuticals, food additives, and animal feeds. The selection and breeding of high-yielding, low-cost, and genetically stable production strains have become a key objective in the L-valine production industry.MethodsUsing Escherichia coli DB-1-1, we developed a screening marker LESG associated with intracellular L-valine levels by choosing GTC, a less common codon for L-valine, in place of all L-valine codons. The artificial LESG was then ligated into pUC-57 and transformed into competent E. coli DB-1-1 cells with the rare L-valine codon. After conducting atmospheric and room-temperature plasma mutagenesis cultures, mutants that displayed elevated fluorescence were sorted using flow cytometry. After sorting the 240 strains. We sorted out 143 highly fluorescent strains, and the sorting efficiency reached 59.5%.ResultsFermentation results showed that the mutant strains with increased fluorescence intensity had an improved L-valine fermentation titer (23.1%) and a higher screening positivity rate (62.5%) than that of the wild-type strain. The maximum titer of valine at 24 h was 84.1 g/L.ConclusionThis approach offers a more comprehensive and effective method for identifying high-yielding L-valine bacterial strains.